(untitled) (Journal of Hama University, 2024)
The research aims to design a model to study the impact of energy carrier prices on the costs of living in Syria and analyze it for a period of 103 months (from 2014-9 to 2023-3) using multiple linear regression, measure its accuracy, and predict through it the costs of living for a Syrian family. The study reached a multiple linear regression model between the prices of energy carriers and the cost of living for the Syrian family. The variables that had the most influence on the dependent variable were identified according to the regression, which are the price of subsidized diesel (a direct relationship), the price of subsidized gasoline (a direct relationship), and the price of non-subsidized diesel (a direct relationship). Inverse), the price of non-subsidized domestic gas (direct relationship), as it was shown that there is a strong correlation between the dependent variable, the food cost of living calculated for the Syrian family, and the independent variables, and that the changes in the cost of living for the Syrian family are due to 75% of the previous independent variables, and the average value reached a terrible error. For the estimated model 9622331956.454, according to the multiple linear regression model by adopting monthly prices in Syrian pounds for the period (2014-9 to 2023-3),This model was adopted according to the statistical standards MSE, RMSE, MAE, and MAPE to predict the time series of the monthly food costs of living for the Syrian family, and it was forecasted for the next 12 months from April 2023 to March 2024, which indicated that the costs of living for the Syrian family are constantly increasing, which affects Life costs.